(untitled) (Delta Medical College Journal, 2014)
Background: Colostrum is the first product of lactation and can be considered as first vaccine for newborns. It contains numerous nutrients as well as antioxidant vitamins necessary for newborns. Objective: The aim of the study was to measure the antioxidant vitamin (vitamins E and C) contents in colostrum and to compare them with the nutritional status, age and parity of the lactating mothers and birth weight of the babies. Materials and method: In this cross sectional study antioxidant vitamins E and C of colostrum of seventy six post-partum mothers were estimated irrespective of their age, parity, socioeconomic and nutritional status. High Performance Liquid Chromatography (HPLC) was employed to analyze the colostral content of vitamin E and spectrophotometric method was used for estimation of vitamin C (ascorbic acid) level. These levels were then compared against maternal and fetal characteristics. Results: The mean concentration (±SD) of vitamin E and C were 519.809(±1.16) ?gm/dl and 1.33(±0.076) mg/dl respectively. No significant relationship was found between maternal age, parity, BMI or birth weight of the baby and the colostral content of vitamin E and C. Conclusion: Colostrum of Bangladeshi women are rich in antioxidant vitamins and not dependent on sociodemographic variables of mothers and / or birth weight of baby. DOI: http://dx.doi.org/10.3329/dmcj.v2i2.20524 Delta Med Col J. Jul 2014; 2(2): 53-57